Influence of ubiquitiform complexity on fracture energy of concrete. Issue 2 (March 2020) - Ju, Yibo; Ou, Zhuocheng; Duan, Zhuoping; Huang, Fenglei
Abstract: The crack extension path of concrete materials was simulated numerically based on the non-uniform numerical model of Weibull distribution, and the complexities of various ubiquitiform fracture surfaces were calculated to explore the relationship between complexity and fracture energy. To study the influence of specific crack extension law and fracture mode on the relationship between the complexity and fracture energy, numerical simulation of the crack extension was carried out based on the numerical model with random aggregate distribution, and the reason for the change of the relationship between complexity and fracture energy were discussed.